An in vitro study to investigate the interference of enoxaparin on plasma levels of direct oral factor Xa inhibitors measured by chromogenic assays. (30th January 2019) - Cini, Michela; Legnani, Cristina; Testa, Sophie; Tripodi, Armando; Cosmi, Benilde; Palareti, Gualtiero
Abstract: Introduction: Co‐administration of enoxaparin and a direct oral factor Xa inhibitor (xabans: apixaban, edoxaban, rivaroxaban) could give rise to the problem of overlapping the anti‐Xa activity when measuring direct oral anticoagulant (DOAC) levels. We aimed to evaluate in vitro the degree of the interference of increasing enoxaparin concentrations on xaban plasma levels measured by different chromogenic anti‐Xa assays with drug‐specific calibrators and controls. Methods: Seven plasma samples were spiked with apixaban, edoxaban, or rivaroxaban at fixed concentration, and enoxaparin at increasing concentrations (0, 0.125, 0.250, 0.50, 1.0, 1.50, and 2.0 IU/mL). The evaluated chromogenic assays were as follows: Biophen DiXaI and Biophen Heparin LRT (Hyphen BioMed), Berichrom Heparin and Innovance Heparin (Siemens), STA‐Liquid Anti‐Xa (Stago Diagnostics), Technochrom anti‐Xa (Technoclone), and HemosIL Liquid Anti‐Xa (Werfen). Results: The presence of enoxaparin caused increased DOAC levels, with over‐estimation depending on the anti‐Xa assay and on the heparin concentration in the sample. The smallest over‐estimation was in the sample with enoxaparin 0.125 IU/mL and the greatest in the sample with enoxaparin 2.0 IU/mL (0%, 3.1%, and 7.4% vs 583.8%, 526.1%, and 415.2% for apixaban, edoxaban, and rivaroxaban, respectively). Biophen DiXaI showed lower interference compared to other methods (maximum over‐estimation in the presence of enoxaparin 2.0 IU/mL: 56.4% dosing rivaroxaban by Biophen DIXaI vs 583.8% dosing apixaban by Berichrom Heparin). Conclusion: The presence of enoxaparin interferes with xabans measurement by chromogenic anti‐Xa assays causing falsely elevated DOAC levels, the over‐estimation being dependent on the anti‐Xa assay and on the heparin concentration in the sample.